Analysis of the Socio-Economic Impact on the Community of Village X Due to the Construction of Hotel X: Analisis Dampak Sosial Ekonomi Masyarakat Desa X Akibat Pembangunan Hotel X - Muhammad Rizal Rosyadi; Okik Hendriyanto Cahyonugroho (Media Ilmiah Teknik Lingkungan (MITL), 2026)
The construction of Hotel X in a Village, has brought various social and economic changes to the surrounding community. This study aims to examine how the project influences local social conditions, levels of concern, community perceptions, employment opportunities, and household income. A descriptive approach was used by combining primary data obtained through field observations and interviews, with secondary data derived from official documents and relevant literature. The findings indicate that most residents are aware of the development plan and generally show a positive response. The community perceives that the presence of the hotel may create new job opportunities and increase income, although a small number of residents still express concerns regarding the changes occurring during the pre-construction and construction phases. These perceptions are shaped by the information received and the direct experiences of the community throughout the development process. Overall, the construction of Hotel X tends to provide economic benefits for the local population; however, proper management of social aspects remains necessary to ensure that the changes are widely accepted and do not generate tension within the community.